2017
DOI: 10.1038/aps.2017.130
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell-derived exosomes promote hematopoietic differentiation of mouse embryonic stem cells in vitro via inhibiting the miR126/Notch1 pathway

Abstract: Cell-derived exosomes (EXs) can modulate target cell differentiation via microRNAs (miRs) that they carried. Previous studies have shown that miR126 is highly expressed in hematopoietic stem cells (HSCs) and plays a role in hematopoiesis via modulating the Notch pathway that participates in progenitors' cell fate decisions. In this study we investigated whether HSC-derived EXs (HSC-EXs) could affect the differentiation of mouse embryonic stem cells (ESCs) into HSCs. We prepared HSC-EXs, HSC-EXs and HSC-EXs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…Mesenchymal stem cell-derived exosomes show a potential effect on the alteration of microRNA profiles and induce osteogenic differentiation, depending on the stage of differentiation, through modulation of the Wnt signalling pathway and endocytosis [254]. Hematopoietic stem cell-derived exosomes promote the hematopoietic diiferentiation of mouse embryonic stem cells through inhibiting the mir126/Notch pathway [255]. Exosomes derived from bladder cancer cells are internalized by fibroblasts and promote the proliferation and expression of CAF markers.…”
Section: Biological Functions Of Exosomesmentioning
confidence: 99%
“…Mesenchymal stem cell-derived exosomes show a potential effect on the alteration of microRNA profiles and induce osteogenic differentiation, depending on the stage of differentiation, through modulation of the Wnt signalling pathway and endocytosis [254]. Hematopoietic stem cell-derived exosomes promote the hematopoietic diiferentiation of mouse embryonic stem cells through inhibiting the mir126/Notch pathway [255]. Exosomes derived from bladder cancer cells are internalized by fibroblasts and promote the proliferation and expression of CAF markers.…”
Section: Biological Functions Of Exosomesmentioning
confidence: 99%
“…Based on published literature, miR concentrations from 1 nM to 3.6 µM have been used to transfect HSPCs. [33][34][35] In the following studies, since the seven MkMP miRs we examined are highly abundant in MkMPs, and due to the fact that multiple MkMPs are taken up by a single recipient CD34 + HSPC, 16 we hypothesized that higher concentrations of these seven miRs are likely delivered to CD34 + HSPC via MkMPs. Therefore, we chose 8 µM of miR mimics for the following experiments.…”
Section: Mir-486-5p In Combination With Mir-22-3p Largely Recapitulatmentioning
confidence: 99%
“…Exosomes were considered to be a mechanism for discarding cell garbage until a number of studies suggested that they were nano-sized vesicles that serve as mediators for intercellular communication through the delivery of proteins, lipids, nucleic acids, or other components in or within their lipid bilayer membrane to neighboring or distant cells. Although accumulating studies have indicated the crucial role of exosomes in various physi-ological and pathological processes, including tumor metastasis, neurodegeneration, and tissue repair [4][5][6][7][8] , the regulation of biogenesis and cargo loading is not fully understood.…”
Section: Introductionmentioning
confidence: 99%